2004
DOI: 10.1111/j.0435-3676.2004.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between solar radiation and the development and morphology of small cirque glaciers (maladeta mountain massif, central pyrenees, spain)

Abstract: Chueca, J. and Julián, A., 2004: Relationship between solar radiation and the development and morphology of small cirque glaciers (Maladeta Mountain massif, Central Pyrenees, Spain). Geogr. Ann., 86 A (1): 81-89.ABSTRACT. Spatial and temporal variations in radiative fluxes influence glacier mass-balance in mountain areas. The primary goal of this study was to assess differences in solar radiation on three glacial cirques located in the Maladeta Mountain massif (Central Spanish Pyrenees), and analyse their impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
1
28
0
3
Order By: Relevance
“…In a catchment in the Yukon, Canada, Pomeroy et al (2003) found that on a clear day at midday in the peak snowmelt period, a 20 • south-facing slope received 80% more incoming solar shortwave radiation than a similarly steep, north-facing slope. This spatial variability leads to significant differences in snowmelt timing and magnitude throughout the basin and can limit melt on nested glaciers in shaded cirques (Chueca and Julián, 2004), limit snow melt (Carey and Woo, 1998;Pomeroy et al, 2003), cause changes in surface temperature (Pomeroy et al, 2003), and limit or increase photosynthesis and therefore affect subsequent vegetation patterns (Dymond, 2002). Chueca and Julián (2004) demonstrated that the spatial distribution of small cirque glaciers could be primarily attributed to the differences in incoming shortwave radiation, primarily due to shading.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In a catchment in the Yukon, Canada, Pomeroy et al (2003) found that on a clear day at midday in the peak snowmelt period, a 20 • south-facing slope received 80% more incoming solar shortwave radiation than a similarly steep, north-facing slope. This spatial variability leads to significant differences in snowmelt timing and magnitude throughout the basin and can limit melt on nested glaciers in shaded cirques (Chueca and Julián, 2004), limit snow melt (Carey and Woo, 1998;Pomeroy et al, 2003), cause changes in surface temperature (Pomeroy et al, 2003), and limit or increase photosynthesis and therefore affect subsequent vegetation patterns (Dymond, 2002). Chueca and Julián (2004) demonstrated that the spatial distribution of small cirque glaciers could be primarily attributed to the differences in incoming shortwave radiation, primarily due to shading.…”
Section: Overviewmentioning
confidence: 99%
“…This spatial variability leads to significant differences in snowmelt timing and magnitude throughout the basin and can limit melt on nested glaciers in shaded cirques (Chueca and Julián, 2004), limit snow melt (Carey and Woo, 1998;Pomeroy et al, 2003), cause changes in surface temperature (Pomeroy et al, 2003), and limit or increase photosynthesis and therefore affect subsequent vegetation patterns (Dymond, 2002). Chueca and Julián (2004) demonstrated that the spatial distribution of small cirque glaciers could be primarily attributed to the differences in incoming shortwave radiation, primarily due to shading. The spatial variability of topographically driven shortwave radiation is important in even gently rolling terrain, as shown by Pohl et al (2006) in a sub-Arctic tundra river basin.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Chueca & Julia´n 2004). Furthermore, where slope is favourable to glacier formation, any convexity in slope will hinder glacier development (Lo´pez-Moreno et al 2006).…”
Section: Local Topographic Controls On Annual Elamentioning
confidence: 99%